Early recognition and access to terminal complement blockers in patients with atypical HUS significantly improves their outcome: a case report - Vanacker, Amelien; Segers, Nathalie; Bael, An; Koninckx, Muriel; Raes, Ann; Vande Walle, Johan; Dehoorne, Joke; Prytula, Agnieszka; Dossche, Lien; Renson, Thomas; Snauwaert, Evelien (Belgian Journal of Paediatrics, 2023)
A 7-year-old boy presented with fever, pruritus and petechiae. Laboratory analysis revealed haemolytic anaemia with presence of schistocytes, thrombocytopenia and acute kidney injury, diagnostic for a thrombotic microangiopathy (TMA). Given the severe clinical presentation, the lack of evidence for verotoxin positive TMA and a normal ADAMTS13, treatment with eculizumab was started. This resulted in a complete resolution of the TMA course with recovery of the kidney injury. Workup revealed high titre of anti-factor H antibodies, diagnostic for an atypical haemolytic uremic syndrome (aHUS). Early recognition and treatment of TMA is essential to optimize the outcome of these patients.